2014
DOI: 10.1136/annrheumdis-2014-205601
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fatty acid content regulates wound repair and the pathogenesis of osteoarthritis following joint injury

Abstract: Objective The mechanisms linking obesity and osteoarthritis (OA) are not fully understood and have been generally attributed to increased weight, rather than metabolic or inflammatory factors. Here, we examined the influence of dietary fatty acids, adipokines, and body weight following joint injury in mouse model of OA. Methods Mice were fed high-fat diets rich in various fatty acids (FAs) including saturated FAs (SFAs), ω-6 polyunsaturated FAs (PUFAs), and ω-3 PUFAs. OA was induced by destabilizing the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
152
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 123 publications
(162 citation statements)
references
References 38 publications
(38 reference statements)
9
152
1
Order By: Relevance
“…This is consistent with the reported increase in palmitate-or stearic acid-induced apoptosis in chondrocytes [225,240]. In addition, previous studies have reported that SFA-rich high-fat diet increased the severity of OA [12,121,160].…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…This is consistent with the reported increase in palmitate-or stearic acid-induced apoptosis in chondrocytes [225,240]. In addition, previous studies have reported that SFA-rich high-fat diet increased the severity of OA [12,121,160].…”
Section: Discussionsupporting
confidence: 81%
“…The ω-3 PUFA diet decreased the progression of OA and synovitis, while the ω-6 PUFA and the SFA diet increased the progression of the disease [121]. Thus the study concluded that dietary composition and not body weight was associated with worsening of the disease.…”
Section: Role Of Fa In Osteoarthritismentioning
confidence: 67%
See 3 more Smart Citations